TRANSLATION UNITS - Gulomova Munavvara; Akhmedov Azimjon (Ta’lim innovatsiyasi va integratsiyasi, 2024)
Annotation. A translation unit is the smallest portion of a sentence whose words cannot be translated separately without resulting in a mistranslation or nonsense. This article given information about translation units.